Peran Forum Kerukunan Umat Beragama dalam Menyelesaikan Konflik Keagamaan - Purwandari, Rika; Aprilia, Nurhaliza; Sir, Tomi Aziz Khan (Letiges, 2022)
A report by the Forum for Religious Harmony (FKUB) found that Medan was the province with the highest annual rate of violations. As a forum initiated by the Ministry of Religion, FKUB has a strategic role in dealing with religious conflicts. Aims to provide a systematic, realistic and accurate picture or description of the news, characteristics and relevance of phenomena investigated by FKUB in conflict resolution in East Medan, North Sumatra. This study uses a qualitative narrative method and social anthropological methods. The existence of FKUB as a complete material unites religious people in service, the desired network, and at the same time the resolution of inter-religious conflicts and Pancasila and the three pillars of development (NKRI, Democracy, Unity in Diversity) as a guide.